2014
DOI: 10.1007/s40262-014-0176-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Microdose Study of [14C]Paracetamol to Study Drug Metabolism Using Accelerated Mass Spectrometry: Proof of Concept

Abstract: Background Pediatric drug development is hampered by practical, ethical, and scientific challenges. Microdosing is a promising new method to obtain pharmacokinetic data in children with minimal burden and minimal risk. The use of a labeled oral microdose offers the added benefit to study intestinal and hepatic drug disposition in children already receiving an intravenous therapeutic drug dose for clinical reasons. Objective The objective of this study was to present pilot data of an oral [14 C]paracetamol [ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 31 publications
0
72
0
Order By: Relevance
“…Full metabolic profiles can be generated as an early indication of the drug's metabolism in humans or absolute bio-availability can be estimated [51,52]. More recently, the practice of microdosing has extended to other areas of drug development, including in vivo drug--drug interactions in human adults, but also explorative studies in special populations, including newborns [53][54][55]. This practice builds further on clinical experience with the use of stable isotopes in neonates to quantify carbohydrate, fat and amino acid metabolism or synthesis of specific peptides or proteins [56].…”
Section: Microdosing and Microtracersmentioning
confidence: 99%
See 2 more Smart Citations
“…Full metabolic profiles can be generated as an early indication of the drug's metabolism in humans or absolute bio-availability can be estimated [51,52]. More recently, the practice of microdosing has extended to other areas of drug development, including in vivo drug--drug interactions in human adults, but also explorative studies in special populations, including newborns [53][54][55]. This practice builds further on clinical experience with the use of stable isotopes in neonates to quantify carbohydrate, fat and amino acid metabolism or synthesis of specific peptides or proteins [56].…”
Section: Microdosing and Microtracersmentioning
confidence: 99%
“…The high sensitivity of the above-mentioned analytic technologies (AMS, LC/MS/ MS) facilitates PK studies by reduction of the sample volumes needed. To the very best of our knowledge, there are at present two compounds ( 14 C-ursodiol and paracetamol) to illustrate at least the feasibility to apply such study methodology (microdosing, microtracer) in neonates [53][54][55]. Gordi et al reported on the repeated administration of 14 C-ursodiol microdosing in 5 non-cholestatic and 3 cholestatic newborns, together with 40 mg/kg of non-labeled ursodiol [54].…”
Section: Microdosing and Microtracersmentioning
confidence: 99%
See 1 more Smart Citation
“…Microdosing pharmacokinetic study with radioactive labeled drug [94] No potential benefit to patient despite safe radiation dose: 'gate-keeping' by physicians and/or nursing staff out of fear for radiation-related negative outcomes. Possible misunderstanding of minimal risks by parents …”
Section: Resultsmentioning
confidence: 99%
“…Microdosing is also used in cases where pharmacokinetics cannot confidently be predicted from preclinical animal species, or to investigate or confirm metabolic routes in humans. Furthermore, it enables investigation of pharmacokinetics in specific target populations (patients, children) that would not be admissible in high-dose phase I trials [10,11].…”
Section: Introductionmentioning
confidence: 99%